Toward a Common Language for Measuring Patient Mobility in the Hospital: Reliability and Construct Validity of Interprofessional Mobility Measures. Issue 2 (2nd November 2017) - Hoyer, Erik H; Young, Daniel L; Klein, Lisa M; Kreif, Julie; Shumock, Kara; Hiser, Stephanie; Friedman, Michael; Lavezza, Annette; Jette, Alan; Chan, Kitty S; Needham, Dale M
Abstract: Background: The lack of common language among interprofessional inpatient clinical teams is an important barrier to achieving inpatient mobilization. In The Johns Hopkins Hospital, the Activity Measure for Post-Acute Care (AM-PAC) Inpatient Mobility Short Form (IMSF), also called "6-Clicks, " and the Johns Hopkins Highest Level of Mobility (JH-HLM) are part of routine clinical practice. The measurement characteristics of these tools when used by both nurses and physical therapists for interprofessional communication or assessment are unknown. Objective: The purposes of this study were to evaluate the reliability and minimal detectable change of AM-PAC IMSF and JH-HLM when completed by nurses and physical therapists and to evaluate the construct validity of both measures when used by nurses. Design: A prospective evaluation of a convenience sample was used. Methods: The test-retest reliability and the interrater reliability of AM-PAC IMSF and JH-HLM for inpatients in the neuroscience department (n = 118) of an academic medical center were evaluated. Each participant was independently scored twice by a team of 2 nurses and 1 physical therapist; a total of 4 physical therapists and 8 nurses participated in reliability testing. In a separate inpatient study protocol (n = 69), construct validity was evaluated via an assessment of convergent validity with other measures of function (grip strength, Katz Activities of Daily Living Scale, 2-minute walk test, 5-times sit-to-stand test) used by 5 nurses. Results: The test-retest reliability values (intraclass correlation coefficients) for physical therapists and nurses were 0.91 and 0.97, respectively, for AM-PAC IMSF and 0.94 and 0.95, respectively, for JH-HLM. The interrater reliability values (intraclass correlation coefficients) between physical therapists and nurses were 0.96 for AM-PAC IMSF and 0.99 for JH-HLM. Construct validity (Spearman correlations) ranged from 0.25 between JH-HLM and right-hand grip strength to 0.80 between AM-PAC IMSF and the Katz Activities of Daily Living Scale. Limitations: The results were obtained from inpatients in the neuroscience department of a single hospital. Conclusions: The AM-PAC IMSF and JH-HLM had excellent interrater reliability and test-retest reliability for both physical therapists and nurses. The evaluation of convergent validity suggested that AM-PAC IMSF and JH-HLM measured constructs of patient mobility and physical functioning.